Measurement of the penetration of 56 cosmetic relevant chemicals into and through human skin using a standardized protocol. Issue 3 (22nd December 2019) - Hewitt, Nicola J.; Grégoire, Sébastien; Cubberley, Richard; Duplan, Hélène; Eilstein, Joan; Ellison, Corie; Lester, Cathy; Fabian, Eric; Fernandez, Julien; Géniès, Camille; Jacques‐Jamin, Carine; Klaric, Martina; et al.
Abstract: OECD test guideline 428 compliant protocol using human skin was used to test the penetration of 56 cosmetic‐relevant chemicals. The penetration of finite doses (10 μL/cm 2 ) of chemicals was measured over 24 hours. The dermal delivery (DD) (amount in the epidermis, dermis and receptor fluid [RF]) ranged between 0.03 ± 0.02 and 72.61 ± 8.89 μg/cm 2 . The DD of seven chemicals was comparable with in vivo values. The DD was mainly accounted for by the amount in the RF, although there were some exceptions, particularly of low DD chemicals. While there was some variability due to cell outliers and donor variation, the overall reproducibility was very good. As six chemicals had to be applied in 100% ethanol due to low aqueous solubility, we compared the penetration of four chemicals with similar physicochemical properties applied in ethanol and phosphate‐buffered saline. Of these, the DD of hydrocortisone was the same in both solvents, while the DD of propylparaben, geraniol and benzophenone was lower in ethanol. Some chemicals displayed an infinite dose kinetic profile; whereas, the cumulative absorption of others into the RF reflected the finite dosing profile, possibly due to chemical volatility, total absorption, chemical precipitation through vehicle evaporation or protein binding (or a combination of these). These investigations provide a substantial and consistent set of skin penetration data that can help improve the understanding of skin penetration, as well as improve the prediction capacity of in silico skin penetration models. Abstract : The penetration of 56 chemicals was tested in human skin using a standard protocol. Dermal delivery correlated with the amount in the receptor fluid (RF). The impact of solvent on penetration was evaluated. Despite finite doses being applied, different profiles of cumulative absorption kinetics into the RF were observed. These data may help understand skin penetration and improve the prediction capacity of in silico skin penetration models.